Anonymizing region construction scheme based on query range in location-based service privacy protection - Zhuo-xiong PEI; Xing-hua LI; Hai LIU; Kai-yue LEI; Jian-feng MA; Hui LI (Tongxin xuebao)
Since k-anonymity method can reduce the users’ computation cost and provides the precise query results,it has been widely used to protect the user’s privacy in location-based service.However,the existing schemes did not consider the size of the querying region for location based service provider (LSP) during the construction of the anonymizing region,which led that the quality of service was low.To solve this problem,the user’s querying range was introduced to present a novel anonymizing region construction scheme.In the proposal,the anonymity server first generated the original anonymizing sub-regions according to the user’s privacy requirements,and then merged these sub-regions to construct the anonymity region submitted to LSP based on the size of corresponding querying regions.The security and experiment analysis show that the presented scheme not only protects the user’s privacy effectively,but also decreases LSP’s querying regions,thereby improving the quality of service.